Pan-vaccinomics strategy for developing a universal multi-epitope vaccine against endocarditis-related pathogens - Chao, Peng; Zhang, Xueqin; Zhang, Lei; Ma, Wei; Wang, Dong; Yang, Aiping; Chen, Xiaoyang (Frontiers in Immunology, 2025)
IntroductionEndocarditis is a life-threatening infection of the heart valves, frequently caused by pathogenic bacteria. The growth of multidrug-resistant bacteria necessitates the development of innovative therapeutic techniques, such as vaccines.MethodsThe current study employed core proteome analysis and a computational-based reverse vaccinology approach across multiple bacterial pathogens associated with endocarditis to identify prospective universal vaccine candidates. The core proteome analysis contained 121 highly pathogenic strains from ten distinct pathogens (Streptococcus mutans, Streptococcus viridans, Streptococcus pyogenes, Staphylococcus aureus, Enterococcus faecalis, Streptococcus agalactiae, Gemella morbillorum, Streptococcus pneumonia, Enterococcus faecium, and Streptococcus gallolyticus). The core proteome was subjected to a subtractive proteomics methodology.ResultsThree proteins that were virulent, non-homologous, antigenic, and non-allergenic have been identified as prospective candidates for vaccine development: 30S ribosomal protein S13, 50S ribosomal protein L6, and UMP Kinase. B and T cell epitopes were predicted from vaccine candidate proteins using a range of immune-informatics methods. An in silico vaccine was created by using meticulously chosen epitopes—seven Cytotoxic T lymphocyte (CTL), seven Linear B lymphocyte (LBL), and three Helper T lymphocyte (HTL) epitopes—and subsequently aligning them with the major histocompatibility complex (MHC) molecules (MHC I & MHC II) and human TLR4. A Cholera toxin subunit B (CTB) adjuvant was added to the vaccine to enhance the immunological response. The molecular interactions and binding affinity of the vaccine with TLR4 and MHC molecules were analyzed using molecular dynamics (MD) simulations and molecular docking. To ensure optimal vaccine protein expression, the vaccine was cloned and reverse-translated in E. coli.DiscussionThis methodology tackles the difficulties presented by the diversity of pathogens and antibiotic resistance, providing a strategic option for developing efficient and durable vaccines against infections associated with endocarditis.